Microstructure, erosion and tribological behaviour of thick DLC coatings by the filtered cathodic vacuum arc combined with a high-voltage pulse power. (9th June 2021) - Shen, Yongqing; Luo, Jun; Liao, Bin; Zhang, Xu; Zhao, Yuanyuan; Chen, Lin; Pang, Pan; Zeng, Xinmiao
Abstract: Hydrogen-free diamond-like carbon (DLC) films with thickness of 36 μ m and 50 μ m have been prepared on Si and AISI 304L stainless steel substrates, respectively, by filtered cathodic vacuum arc (FCVA) together with a high-voltage pulse power. The structure, chemical bonding state, mechanical properties and wear, corrosion resistance and anti-erosion performance were evaluated. The thick DLC films with compressive stress of 0.71 GPa and hardness of 3160 HV were obtained. The preparation of the low stress but high hardness coating mainly due to the appropriate high negative bias and short pulse duration, which could result in an alternate ion bombardment and deposition. The 50 μ m-thick coating showed corrosion resistance with high polarization resistance of 4.69 × 10 8 Ω·cm 2 and low corrosion current density of 5.47 × 10 −8 A·cm −2 . Thick coating exhibited outstanding sand particle erosion resistance with low average mass loss rate of 0.035 mg g −1 . Under high-speed sand erosion conditions, the coating remains unbroken, without peeling or cracking were observed on the erosion center. In addition, DLC coatings showed good tribological performance under dry, water- and oil-lubricated condition.